Demolition Protocol & Best Local Practice for the Western Australian Construction and Demolition Industry - Whyte, Andrew; Marshall, Nicholas (RICS, 2011)
There is currently no best practice demolition guidance for the West Australia (WA) construction and demolition industry. The work presented here sought to address this need. Development (and subsequent validation) of an optimum, local best demolition practice tool was determined through consideration of: industrial need; environmental impact; and, economic viability, resulting in a resource efficient demolition protocol for WA. The developed protocol was then applied to specific case studies to guide local practice. Primary data generation produced results indicating that both potential environmental and economic benefits are achievable through the application of resource efficient demolition practices. It is concluded that the application of a resource efficient demolition protocol applied to current activities in WA can result in both environmental and economic benefits; translated as significant measureable CO2 emission reductions (emission benefit of 65,734.2 kgCO2 per site) as well as an Aus$14/tonne saving in the processing of arising demolition materials.